Islamic work ethics, good corporate governance practices and fraudulent financial statements / Reskino … [et al.] - -, Reskino; Mohamed, Intan Salwani; Mohamed, Norazida; Sulistyowati, Endah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
This study examined the effects of Islamic work ethics (IWE) and good corporate governance (GCG) on fraudulent financial statements (FFS) in Islamic financial institutions (IFIs). The study used a questionnaire survey to examine the relationship between IWE and GCG practises on FFS in IFIs. The finding revealed that IWE and GCG practices significantly influenced FFS through fraud prevention. This study gives banking and insurance professionals a practical grasp of the aspects to consider in the fight against fraud in financial statements. This is the first study that gives empirical evidence of the importance of Islamic work ethics in fraud prevention and its impact on FFS in IFIs in the context of Indonesia, the country with the highest Muslim population. This study suggests that policymakers and the financial services authorities should redouble their efforts to prevent fraudulent financial statements by instituting an effective anti-fraud strategy and integrating Sharia compliance auditing standards. These findings can also assist internal auditors around the globe in identifying the indicators that management may be considering FFS, thereby decreasing the likelihood of fraud occurring.